Biologically Active Saponins From Bougainvillea spectabilis Growing in Egypt - H. Ahmed, Amal (Asian Journal of Chemistry, 2010)
Three triterpenoidal saponins 3,23-dihydroxy-12-oleanen-28-oic acid, 3-O-[α-L-rhamnopyrosyl-(1→2)-α-L-arabinopyranoside]-28-O- [α-L-rhamnopyrosyl(1→4)-β-d-glucopyranosyl-(1→6)-β-D-glucopyranoside; 3-O-β-D-glucopyranosyl-1(1→2)-β-D-glucopyranosyl- (1→4)-α-L-rhamnopyranoside quinovic acid and 3,23-dihydroxy-12- oleanen-28-oic acid-3-O-[α-D-glucopyranosyl-(1→4)-α-D-glucopyranoside]- 28-O-[α-D-glucopyranoside] were isolated for the first time from the methanolic extract of the leaves of Bougainvillea spectabilis (Family: Nyctaginaceae). The structure of the isolated compounds had been established on the basis of several spectral techniques. Biological screening revealed that they have a significant strong antibacterial activity against Escherichia coli, Salmonella typhi, Pseudomonas aeruginosa, Bacillus subtilis and Staphylococcus aureus and no cytotoxic activity either on Ehrlich ascities carcinoma cell line or on different types of human cancer cell lines.